2023
DOI: 10.1098/rstb.2022.0102
|View full text |Cite
|
Sign up to set email alerts
|

Selective selfishness in alarm calling behaviour by some members of wintering mixed-species groups of crested tits and willow tits

Abstract: Animals adjust their use of alarm calls depending on social environments. We tested whether dominant (adult) and subordinate (juvenile non-kin) male crested tits ( Lophophanes cristatus ) warn each other and heterospecific willow tits ( Poecile montanus ) across the wintering season. Birds rarely alarm called when feeding alone. Both adult and juvenile crested tits warned each other in early winter, and adults did so in the middle of wintering season. However, ju… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…We increasingly understand how signals and cues used by senders and receivers across species boundaries facilitate and maintain mixed-species groups [48][49][50]. A recent study, for example, has found that young crested tits, Lophophanes cristatus, are more likely to produce alarm calls in the winter and early spring months when they are in flocks with willow tits, Poecile montanus, than when they are alone or in flocks with just conspecifics [51].…”
Section: Plos Onementioning
confidence: 99%
“…We increasingly understand how signals and cues used by senders and receivers across species boundaries facilitate and maintain mixed-species groups [48][49][50]. A recent study, for example, has found that young crested tits, Lophophanes cristatus, are more likely to produce alarm calls in the winter and early spring months when they are in flocks with willow tits, Poecile montanus, than when they are alone or in flocks with just conspecifics [51].…”
Section: Plos Onementioning
confidence: 99%